Control of a 3-Phase 12/8 Switched Reluctance Generator for Future Energy System Applications - Phop Chancharoensook (My University, 2024)
This paper presents implementation of a control system for a 3-phase 12/8 switched reluctance generator (SRG). The study has confirmed the potential of switched reluctance machines to be decent alternatives in renewable energy applications, energy storage systems and electrified transportation systems. Initially, a dynamic model of the SRG was created in MATLAB/Simulink environment to achieve useful preliminary results from computer simulation. Next, in hardware realization, the proposed system employed a standard asymmetric half-bridge (AHB) converter to generate a voltage of 200 V at the DC-link. Optimal turn-on and turn-off angles of phase current waveforms were used through commutation signals generated by a simple and inexpensive opto-interrupter rotor position sensor. There were two closed-loop controls involved in the system. The outer loop was for DC-link voltage control using PI controller while the inner loop was for phase current control using soft chopping hysteresis control technique. Finally, real-time control was implemented using an economical dsPIC30F4011 microcontroller. Experimental results have shown acceptable performance of the proposed SRG control system in various conditions, including normal operation, speed change and step reference voltage change. The DC-link voltage can be satisfactorily regulated when subjected to those conditions.
Keywords: Electric Motor Design and Analysis; Induction Heating and Inverter Technology; Multilevel Inverters and Converters